Avaliação isocinética do ombro após procedimento cirúrgico de Bristow/Latarjet em atletas - Ribeiro, Leandro Masini [UNIFESP] (2019)
Introduction: Anterior shoulder instability can be a disabling condition for the young athlete. The Bristow / Latarjet stabilization procedure is a valid and safe surgical treatment for recurrent anterior shoulder instability in patients with bone and capsular deficit. Isokinetic evaluation can serve as a useful tool for shoulder evaluation after surgery. Objectives: To evaluate the muscular strength of the internal and external rotators of the shoulder after Bristow / Latarjet surgery. Methods: The present study is of the cross-sectional with 18 patients (36 shoulders). The isokinetic evaluation was performed using the Biodex 3 System Pro® dynamometer. The EROE (Sportsman Shoulder Outcome Assessment Scale) and VAS (Visual Analogue Scale) scales were applied. Results: The sample was characterized by a mean age of 26.7 years, with a return to sport of 4.81 months, EROE (M = 91.0) and VAS (M = 0.44). Men represented 94.44% (n = 17) of the patients. The values of peak torque and maximum work in concentric and eccentric mode on the non-operated shoulder were higher than on the operated side for both the internal (IR) and external (ER) rotators, p≤0.01. The conventional and functional balance between the ER and IR showed no differences between the operated versus non-operated side. When comparing patients with postoperative time <1 year or ≥1 year, no differences were observed in peak torque values at 60°/s and 240°/s and maximum work at 60°/s and 240°/s of IR to the operated shoulder. However, peak torque values of 60°/s and 240°/s and maximum work at 60°/s and 240°/s of ER were higher in subjects with postoperative time ≥1 year in all variables, p<0.05. According to the angular loss of ER, for the operated shoulder no differences were observed in any isokinetic variable. Conclusions: We found a decrease in the strength of the IR and ER in the operated shoulder compared to the healthy shoulder. However, the conventional and functional balance was maintained. The loss of range of motion at 10 degrees of external rotation did not influence the loss of strength.